School and Teacher in the Light of the Contemporary Challenges for Health Promotion of Children and Youth - Anna Gaweł (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Health promotion in schools includes health education and actions aimed at creating an environment conducive to the physical and psychosocial health of students. This process is conditioned by educational and organizational factors and factors which are related to the competence of teacher. In fact today the particular context of actions taken by the school is created by a socio-cultural factors. The author analyzes the assumptions of health education program in school, academic curricula of teachers and selected aspects of the school environment and she sees in them the barriers to the effectiveness of health promotion in school.